PENGARUH KECUKUPAN MODAL, TINGKAT EFISIENSI, RISIKO KREDIT, DAN LIKUIDITAS PADA PROFITABILITAS LPD KABUPATEN BADUNG - Ariani, Made Windi; Ardiana, Putu Agus (E-Jurnal Akuntansi, 2015)
LPD as a driver of economic development in the traditional village environment has an important role to improve the welfare of rural communities in particular manners. The existence of LPD in Badung regency has increased. These developments must be followed by good financial performance in which the views of the ability to generate profit by LPD. Inconsistencies regarding the profitability derived from the results of previous studies, the researchers aimed to investigate the effect of capital adequacy, efficiency rate, credit and liquidity risk on profitability. The study was conducted in LPD Badung with proportional random sampling method in order to obtain a total sample of 94 units of LPD. The analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that the capital adequacy ratio (CAR) has no effect on profitability (ROA), the level of efficiency (ROA) negative effect on profitability, credit risk (NPL) negative effect on profitability (ROA), and liquidity (LDR) has positive effect on profitability.
Keywords: Capital Adequacy Ratio (CAR), Level of Efficiency (ROA), Credit Risk (NPL), Liquidity (LDR), profitability (ROA)